DETERMINASI TAX AVOIDANCE : EFEK MODERASI UKURAN PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI - Listiorini Listiorini; Muhammad Arief; Zuwina Miraza; Mhd. Triansyah Putra (Universitas Dharmawangsa, 2026)
This study aims to examine accounting conservatism, audit quality, and return on assets in relation to tax avoidance, with company size as a moderating variable in consumer goods manufacturing companies listed on the IDX from 2018 to 2023. This study uses a quantitative method with a population of manufacturing companies in the consumer goods industry listed on the IDX. Sampling was conducted using purposive sampling, resulting in a sample size of 228. Data analysis was performed using moderated regression analysis (MRA) with the EViews 12 data processing application. The findings reveal that accounting conservatism has a positive influence on tax avoidance, while audit quality does not exhibit a significant effect. In contrast, ROA has a negative impact on tax avoidance. Furthermore, firm size weakens the relationship between accounting conservatism and tax avoidance and fails to moderate the influence of audit quality. However, firm size strengthens the relationship between ROA and tax avoidance..